THE LEGENDARY JUSTICE BAO : GUARDIAN OF TRUTH. 2 - Yap, Aloysius; Heymans, Shaul (Singapore : WS Education, 2023)
Throughout the centuries, people have recounted tales of a legendary magistrate known as Justice Bao! Never letting anything stand in the way of his pursuit for truth and justice, Justice Bao was a clever and upright official who never failed to solve his cases. He was liked by all who sought justice, and feared by criminals everywhere. In this second book of Justice Bao's adventures, you will discover the keen intelligence and masterful skill of a well-respected figure who remains a household name in many parts of the world!
"2"--Spine.
Keywords: Bao, Zheng, -- 999-1062 -- Juvenile fiction; Justice -- Juvenile fiction; Children's stories